Green synthesis of anisotropic gold nanoparticles using hordenine and their antibiofilm efficacy against Pseudomonas aeruginosa. Issue 8 (5th October 2017) - Rajkumari, Jobina; Meena, Himani; Gangatharan, Muralitharan; Busi, Siddhardha
Abstract : Pseudomonas aeruginosa is a notorious pathogen that causes biofilm aided infections in patients with cystic fibrosis and burn wounds, resulting in significant mortality in immunocompromised individuals. This study reports a novel one‐step biosynthesis of gold nanoparticles using phytocompound, hordenine (HD), as a reducing and capping agent. The synthesis of the anisotropic hordenine‐fabricated gold nanoparticles (HD‐AuNPs) with an average particle size of 136.87 nm was achieved within 12 h of incubation at room temperature. Both HD and HD‐AuNPs exhibited significant antibiofilm activity against P. aeruginosa PAO1, although greater biofilm inhibition was observed for the nanoparticles as compared to hordenine alone. In the microtitre plate assay and tube method, the nanoparticles significantly inhibited the biofilm formation by 73.69 and 78.41%, respectively. The exopolysaccharide production by the test pathogen was arrested by 68.46% on treatment with the nanoparticles. Further, the effect of HD and HD‐AuNPs on the biofilm architecture of P. aeruginosa was revealed by light and confocal laser‐scanning microscopy micrographs. The overall results of this study suggested the synergistic antibiofilm effect of AuNPs and HD for the treatment of chronic bacterial infections caused by biofilms forming pathogens.